The effect of Public Accountability and Management Control Systems on Organizational Performance with Organizational Culture as a moderation variable - David Pangaribuan; Aldi Supriyanto (Media Ilmiah Akuntansi, 2021)
Every organization will try to realize the goals that have been set previously. This study aims to examine: (1) the effect of public accountability on organizational performance, (2) the effect of management control systems on organizational performance, (3) the effect of public accountability on organizational performance through organizational culture as a moderating variable, (4) the influence of management control systems. on organizational performance through organizational culture as moderation. This type of research is descriptive quantitative research using multiple linear regression. Data collection techniques using questionnaires and sampling techniques using purposive sampling with 60 respondents based on certain criteria, with positions as head of sub-section (head of sub-section) and executor (staff) at the Regional Secretariat of South Tangerang City. The research was conducted in 2020, with the following research results: (1) Public accountability has a positive and significant effect on organizational performance. (2) The management control system has a positive and significant effect on organizational performance. (3) Organizational culture moderates the relationship between public accountability and organizational performance and (4) Organizational culture moderates the relationship between management control systems and organizational performance. The implication of the research result is that public accountability, management control system and organizational culture have an important role in improving organizational performance. Therefore, these three variables need attention so that they can be maintained.